2023
DOI: 10.1001/jamanetworkopen.2023.4680
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dietary Fiber Intake With Gastrointestinal Tract Cancer Among Korean Adults

Abstract: This cohort study assesses the association between dietary fiber intake and incident gastrointestinal tract cancer among Korean adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…137 In a Korean study that included 9246 participants, DF intake at or above the median was associated with a reduced risk of GIC. 138 In addition to GIC, a study that included more than 1 445 850 adults found that DF intake was negatively associated with lung cancer risk. 139 Interestingly, numerous studies have also demonstrated that human dietary intake of DF reduces the incidence of several other cancers, including oral, prostate, liver, and breast.…”
Section: Cancermentioning
confidence: 99%
“…137 In a Korean study that included 9246 participants, DF intake at or above the median was associated with a reduced risk of GIC. 138 In addition to GIC, a study that included more than 1 445 850 adults found that DF intake was negatively associated with lung cancer risk. 139 Interestingly, numerous studies have also demonstrated that human dietary intake of DF reduces the incidence of several other cancers, including oral, prostate, liver, and breast.…”
Section: Cancermentioning
confidence: 99%